(untitled) (Al-Academy, 2024)
Technology has contributed to creating a new space for the theatrical experience, and technology has become a major element of it, especially at the present time. Many directors have employed it, certainly not for the sake of keeping up with reality, but because it is an artistic and aesthetic necessity that has formed a new communicative space between the theatrical performance and the recipient. It contributed to building creative forms close to society, its problems, and its cultural borders.Based on this, the researcher set out to choose the topic of this research, entitled (Technology and the formation of identity in the performance of the Iraqi theatrical actor - a Facebook play as an example), which included an introduction to the research, which contained the research problem that revolved around the question: (What is the role of technology in the formation of identity?) How is the effect of the dialectic of the relationship between technology and identity in the performance of the Iraqi theatrical actor?) To achieve the goal of the research, which was to identify the nature of the relationship between technology and identity and reveal its effective dialectics in crystallizing the acting performance of the Iraqi theatrical actor. As well as the importance of research, its limitations, and definition of terms.The research dealt with (theoretical foundation), which included two sections, the first of which was performance as identity, while the second section showed the role of technology in forming identity according to the formats of theatrical performance. The research in (research procedures) dealt with an analysis of the research sample, which was represented by the Iraqi theatrical performance (Facebook). The research concluded with a set of results and conclusions.